Неки аспекти испитивања словенских паралела грчке речи ὰρχιερεύς у црквенословенским јеванђељским и апостолским текстовима српске редакције у XII, XIII и XIV веку - Stefanović, Dimitrije (Balcanica - Annual of the Institute for Balkan Studies, 1979)
Some Aspects of Investigating the Slav Parallels of the Greek Word ὰρχιερεύς in Church Slavonic Gospel and Epistles Texts of Serbian Redaction in the 12th, 13th and 14th Centuries The Slav lexems which appear as the result of taking over resp. of translating the Greek New Testament word ὰρχιερεύς in the Church Slavonic Gospel and Epistles texts of Serbian redaction of a determined period are examined in the present paper from the textologic and semantic aspects.